2015
DOI: 10.19027/jai.14.128-134
|View full text |Cite
|
Sign up to set email alerts
|

The growth of eel fed with different protein level and protein-energy ratio

Abstract: PENDAHULUANAnguilla bicolor bicolor merupakan salah satu jenis ikan sidat yang banyak dibudidayakan di Indonesia dan termasuk ke dalam jenis ikan karnivora yang memiliki pertumbuhan yang lambat. Pertumbuhan ikan sidat dalam satu siklus pemeliharaan dari benih ukuran glass eel (0,09-0,12 g) mencapai ukuran konsumsi (250 g) membutuhkan waktu sembilan bulan sampai dua tahun bahkan beberapa di antaranya terhenti pada ukuran 2-3 g. ABSTRACTThe study was aimed to determine the optimum dietary protein level and ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
0
9
1
1
Order By: Relevance
“…Survival rate during this study was observed at 100% in all treatments. This indicates that the feed quality given to the entire treatments was able to fulfill snakehead fish nutrient requirements and proved that the feeding rate and aquatic environment were suitable to meet basic terms of fish to live and grow (Nawir et al, 2015).…”
Section: Discussionmentioning
confidence: 78%
“…Survival rate during this study was observed at 100% in all treatments. This indicates that the feed quality given to the entire treatments was able to fulfill snakehead fish nutrient requirements and proved that the feeding rate and aquatic environment were suitable to meet basic terms of fish to live and grow (Nawir et al, 2015).…”
Section: Discussionmentioning
confidence: 78%
“…The protein content of feed B which was higher than the other treatments was seen to be able to meet the protein requirement for the growth of giant prawns (Table 1). According to Palinggi [6] and Nawir [7] a higher protein content to a certain amount will result in better growth in fish. This happens because fish require high levels of protein to a certain level to meet the body's protein needs In addition, the high growth of giant freshwater prawns in feed B was thought to be due to the availability of essential amino acids such as valine, leucine, lysine isoleucine and so on (which played a role in increasing fish growth) in sufficient quantities in feed B (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Pemanfaatan protein dalam tubuh tergantung dari ketersediaan sumber energi nonprotein dalam pakan yang selanjutnya akan memengaruhi pertumbuhan, konversi pakan, efisiensi retensi nutrisi dan komposisi tubuh (Khan & Abidi, 2012). Kinerja pertumbuhan yang optimal pada ikan sidat dapat dicapai oleh kadar protein berkisar antara 45,38-49,60% (Nawir et al, 2015).…”
Section: Hasil Dan Bahasanunclassified